Testing of the Effectiveness of Galangal Leaf Extract (Alpnia Galanga) on the Death of Culex Sp Larvae - Apriyani Pramudiyawati Yunar; Reni Anggraeni; Rita Putri Wati; Panduwita; An'nisaa Heriyanti (Formosa Journal of Multidisciplinary Research, 2024)
With the increase in population, the breeding and breeding places for Culex sp mosquitoes are also increasing. Where these mosquito larvae like to live in puddles of clean water and dirty water so that the density of Culex sp larvae is higher. Controlling disease vectors is a priority in disease control efforts because the potential for transmitting disease is very large, such as flies, mosquitoes, mice and other insects. Vector control activities can include spraying, biological control, eradicating mosquito nests and improving the environment. Efforts to control vectors, especially mosquitoes, can start from controlling the larvae. Control of mosquito larvae usually uses larvicide containing the active ingredient temephos (an organophosphate group). Galangal (Alpinia galanga) is a long-lived plant, about 1-2 meters high. Usually grows in tight clumps. Galangal leaves are toxic and repellent, and have been tested against Daucus caudatus, Manduca sexta, Aphids, besides having nematocidal activity.The aim of this research was to determine the effectiveness of galangal leaf extract (Alpinia galanga) on the death of Culex sp larvae.From the research results, from 91 ml of galangal leaf extract, a p-value coefficient of 0.03 was obtained, where the p-value <0.05 means the relationship between galangal leaf extract and larval death. From 92 ml of galangal leaf extract, a p-value coefficient of 0.03 was obtained, where the p-value <0.05 means the relationship between galangal leaf extract and larval death. From 93 ml of galangal leaf extract, a p-value coefficient of 0.06 was obtained, where the p-value <0.05 means the relationship between galangal leaf extract and larval death. From 94 ml of galangal leaf extract, a p-value coefficient of 0.00 was obtained, where the p-value <0.05 means the relationship between galangal leaf extract and larval death.It is hoped that the public can use galangal leaf solution in breeding places for Culex sp mosquitoes such as water reservoirs, used tires, etc. Providing information to the public in the form of posters or brochures containing the benefits of kemagi leaf extract which can be used as a vegetable insecticide in an effort to control the Aedes aegypti mosquito population.